2022
DOI: 10.1038/s41598-022-25509-3
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila suzukii energetic pathways are differently modulated by nutritional geometry in males and females

Abstract: As a polyphagous pest, Drosophila suzukii has a variety of host fruits available for feeding and oviposition, but how the nutritional geometry of different hosts influences its metabolism is still poorly understood. This work aimed to evaluate how D. suzukii metabolic and transcriptional pathways are influenced by feeding on different host fruits, and how sex influences these responses. Adult flies were allowed to feed on five different fruit-based media. Lipids, glucose, glycogen, and energy pathways-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Eggs and larvae were obtained by collecting ripe-infested blueberries from this field. The colony was housed in plastic vials containing standard drosophila cornmeal diet [1.5% ( w / v ) agar, 4% ( w / v ) brewer’s yeast, 8% ( w / v ) cornmeal, 10% ( w / v ) sugar, 0.08% ( w / v ) methyl 4-hydroxybenzoate, 0.15% ( v / v ) orthophosphoric acid, and distilled water (dH 2 O)] [ 30 ], at 23 °C under a 16:8 h of light:dark photoperiod, and was transferred to new vials every week. In every survival experiment, 2–5 days-old flies were used (five males and five females per experimental vial).…”
Section: Methodsmentioning
confidence: 99%
“…Eggs and larvae were obtained by collecting ripe-infested blueberries from this field. The colony was housed in plastic vials containing standard drosophila cornmeal diet [1.5% ( w / v ) agar, 4% ( w / v ) brewer’s yeast, 8% ( w / v ) cornmeal, 10% ( w / v ) sugar, 0.08% ( w / v ) methyl 4-hydroxybenzoate, 0.15% ( v / v ) orthophosphoric acid, and distilled water (dH 2 O)] [ 30 ], at 23 °C under a 16:8 h of light:dark photoperiod, and was transferred to new vials every week. In every survival experiment, 2–5 days-old flies were used (five males and five females per experimental vial).…”
Section: Methodsmentioning
confidence: 99%
“…The capacity of D. suzukii females to feed and lay eggs in a wide variety of cultivated and non-cultivated host species allows this pest to have access to reproduction sites and feeding sources year-round [22][23][24][25]. We have recently demonstrated that the nutrition source modulates D. suzukii's energetic pathways, in a way dependent on the fruits' nutritional geometry and sex, and that females showed higher adaptability in their energetic metabolism shift to the diet [25]. Energetically more suitable hosts may provide better conditions for feeding and development success of the offspring, and support D. suzukii host preferences [26,27].…”
Section: Migration and Sheltering In Non-crop Habitatsmentioning
confidence: 99%
“…time of the year, type of crop) (Lee et al, 2013). Besides the environmental factors present across dates, it would be important to take into consideration the availability of alternative food resources that might interfere with the bait spray efficacy as it has been suggested that D. suzukii females can rapidly shift their metabolism to adapt to the available food sources (Sario et al, 2022). Also, it would be important to test the baits on non-target (beneficial) organisms, such as pollinators and natural enemies.…”
Section: Discussionmentioning
confidence: 99%